Changes in carbon stocks in Eucalyptus globulus Labill. plantations induced by different water and nutrient availability - Fabião, António (2002)
Changes in the carbon stocks under different soil water and nutrient conditions were studied in Eucalyptus globulus Labill. stands in a field experiment, at O ´ bidos (central Portugal). The treatments were irrigation plus a complete fertiliser solution to simulate ‘near optimal’ nutrition (IF), irrigation only (I), and fertilisers added to rain-fed plots (F). The control (C) received neither water nor fertilisers (except a small amount at planting). The production of biomass (aboveground), the litterfall and the soil chemical composition were evaluated regularly during the experiment. Root biomass was estimated at the end of the experiment. Carbon in biomass, litterfall and soil, increased significantly when water and/or nutrients were supplied, in comparison to the control. The amount of carbon accumulated in the system, 6 years after planting, was 8.22, 10.22, 11.23 and 13.76 kg C m 2 in the control, F, I and IF treatments, respectively. The increase of carbon in the system during the same period was 5.86, 7.86, 8.87 and 11.40 kg C m 2 in the control, F, I and IF treatments, respectively. This rise in carbon resulted from the accumulation of long-lived woody biomass, which represented between 77.7 (in IF) and 82.9% (in the control) of the total rise in carbon. Although water was the main limiting factor for biomass accumulation, the allocation of carbon to the soil was mainly related to nutrient supply, irrespective of water availability. The amount of carbon stored belowground, i.e. soil and forest floor, plus stumps and roots, reached 4.2, 4.7, 4.8 and 6.3 kg C m 2 in the control, F, I and IF treatments, respectively. The increase in C in the mineral soil regarding the initial state was, in the same order as above, 0.21, 0.75, 0.58 and 1.21 kg C m 2. These values were 3.6, 9.6, 6.6 and 10.6% of the C accumulated in the whole system, during the experimental period.